2020
DOI: 10.1075/ni.18090.san
|View full text |Cite
|
Sign up to set email alerts
|

Vivid elements in Dutch educational texts

Abstract: Educational publishers often make their expository texts more vivid, by making them emotionally interesting, concrete and imagery-provoking, and proximate in a sensory, temporal, or spatial way. Previous studies have found mixed results regarding the effects of vividness on the attractiveness, comprehensibility, and memorability of educational texts. In order to be able to account for these mixed results, we chart and describe the various ways in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 114 publications
0
23
0
Order By: Relevance
“…In a previous study, we have shown that Toolan's (2001) definition is well-applicable in the domain of Dutch educational texts, and that a narrative educational text can be characterized as exhibiting the following three narrative elements: 1) a sequence of non-randomly connected particularized events, that are 2) experienced by a specific character, of whom 3) readers gain insight into the inner world (Sangers et al, 2020).…”
Section: Narrativity In the Educational Domainmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we have shown that Toolan's (2001) definition is well-applicable in the domain of Dutch educational texts, and that a narrative educational text can be characterized as exhibiting the following three narrative elements: 1) a sequence of non-randomly connected particularized events, that are 2) experienced by a specific character, of whom 3) readers gain insight into the inner world (Sangers et al, 2020).…”
Section: Narrativity In the Educational Domainmentioning
confidence: 99%
“…However, not all Dutch educational texts prove to be fully expository (Sangers, Evers-Vermeul, Sanders & Hoeken, 2020). For example, the text in (2) presents a narrative about a prehistoric man named Iugas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, fundamental questions about what determines transportation, identification, and effective narrative communication have yet to be answered. Review studies on narratives in health communication and educational texts found numerous differences in the experimental narratives used as stimuli in effect studies, making it difficult to pinpoint the exact determinants of narrative persuasion ( De Graaf et al, 2016 ; Sangers et al, 2020 ). Apart from great variation in length, modality, content, and context, which all inevitably influence the audience’s representation of a narrative, there are clues hinting at the importance of linguistic viewpoint phenomena.…”
Section: Introductionmentioning
confidence: 99%